Гора самоцветов: сказки народов СССР / худ. И. Кузнецов - Кузнецов И. (Детская литература, 1989)
Экземпляры: ф. 1 (20090213) / Инвентарный номер: 65744 / Цена: 11.00 / Авт.знак: Г 67 / ГРНТИ: 17.71 / ББК: 82.3(2)